Explaining the ontological and structural metaphors of the concept of "world" in the poems of Saadi and Parvin - Nahid Behmanesh; Foroogh Kazemi (زبان پژوهی, 2023)
According to the cognitive linguistics approach, language acts as a window to the mind. In other words, it is believed that the patterns of conceptualization in the mind can be discovered through the study of language. One of the most important theories in this approach is the Conceptual Metaphor Theory, which asserts that the conceptual system in the human mind has a metaphorical nature, and metaphors are the most important means of conveying abstract concepts. Metaphorical concepts can extend beyond ordinary literal ways of thinking and talking into the realm of figurative, poetic, or fanciful thought and language. Persian literature, as one of the oldest in the world, consists of numerous works in prose and poetry. Studying these works through the Conceptual Metaphor Theory may provide insights into the dominant thinking of their writers and poets.Sharifi Moghadam and others (2021) conducted research entitled "A Cognitive Analysis of the Concepts of 'Divine Anger and Worldly Punishment' in the Holy Quran." This study investigated the conceptualization of divine anger in the Holy Quran. According to this study, the target domains used in the Quran demonstrate that although divine anger is distinct from human anger, the conceptualization is designed in a way that is easy to understand for human beings. Another study, "A Comparative Study of Metaphor in Massoud Sa'ad and Naser Khosrow's Odes," was conducted by Mobarak and Parsa (2019). This research aims to compare these two poets within intellectual and literary circles by examining the metaphors used by Masood Sa'ad and Nasser Khosrow in their works and exploring their similarities and differences. Through analyzing the meaning, content, application, type, and structure of the metaphors, this study reviews and evaluates one of the important aspects of figurative language in these two works.    One of the abstract concepts that can be observed in the works of great writers and poets is the concept of "world," which is closely related to life and existence. As mentioned, the abstract concept of "world" can be understood through tangible concepts, and investigating its metaphors may provide insights into the attitudes of writers and poets toward life. Therefore, the main focus of this research is to study the ontological and structural metaphors of the "world" concept in Saadi's and Parvin's poems. The main objective of this study is to determine their dominant thinking regarding the world. The study aims to answer the following questions: What is the frequency of ontological and structural metaphors of the "world" concept in Saadi's and Parvin's poems? And what are Saadi's and Parvin's dominant perspectives on the world?